Strategi Pembelajaran di Laboratorium IPA untuk Meningkatkan Aspek Afektif, Kognitif dan Psikomotorik Siswa - Nabilah Juliandari; Leony Rosita Dewi; Lia Angreani (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Laboratory-based learning is an important part of science education because it allows students to connect theory with practice directly. Through laboratory activities, students not only develop conceptual understanding, but also motor skills and positive scientific attitudes. However, the implementation of laboratory learning in schools is often constrained by limited facilities, lack of integrated teaching strategies, and suboptimal use of technology. This study aims to identify and analyze various laboratory learning strategies that are effective in improving students' affective, cognitive, and psychomotor aspects. The method used is a literature study of 15 national scientific articles published in the last ten years. Data were analyzed descriptively qualitatively to evaluate the effectiveness of the various methods applied. The results of the study indicate that the inquiry approach, direct experiments, virtual laboratories, recitations, and collaborative strategies play a significant role in developing students' conceptual understanding, critical thinking skills, motor skills, and positive attitudes. In conclusion, laboratory-based learning strategies that are designed appropriately can improve the quality of science learning holistically and prepare students to face real-world challenges.